Protokolle des Ministerrates der Ersten Republik, Kabinett Dr. Kurt Schuschnigg, Band 8 (4. Juni 1937 - 21. Februar 1938) - Enderle-Burcel, Gertrude (Verlag Österreich GmbH, 2013)
With this volume, the Edition of the Minutes of the Meetings of the Schuschnigg Cabinet (July 29, 1934 to March 11, 1938) comes to a close. The edition of this essential source of Austrian history opens up new scientific perspectives due to the transcription of the minutes' shorthand notes (written using the now obsolete and difficult to read Gabelsberger system) and the comprehensive scientific commentary and explanatory notes. The detailed biographical and subject indices provide a means for easy search within the volumes contents.The Minutes of the Cabinet Meetings have to be regarded as central source materials for Austrian politics.